Black water - MacHale, D. J. (New York : Aladdin Paperbacks, 2004)
Fifteen-year-old Bobby Pendragon places himself, his friends, and the people of Halla in danger in order to protect the territories from a mysterious plague.
"Journal of an adventure through time and space."
5.7
5-8
Keywords: Plague -- Fiction; Space and time -- Fiction; Life on other planets -- Fiction; Time travel -- Fiction; Mystery and detective stories; Adventure and adventurers -- Fiction; Science fiction; Plague -- Fiction; Space and time -- Fiction; Life on other planets -- Fiction; Time travel -- Fiction; Mystery fiction; Adventure fiction; Science fiction